Defining a pro‐inflammatory neutrophil phenotype in response to schistosome eggs. (25th June 2014) - Chuah, Candy; Jones, Malcolm K.; Burke, Melissa L.; McManus, Donald P.; Owen, Helen C.; Gobert, Geoffrey N.
Summary Neutrophils contribute to the pathological processes of a number of inflammatory disorders, including rheumatoid arthritis, sepsis and cystic fibrosis. Neutrophils also play prominent roles in schistosomiasis japonica liver fibrosis, being central mediators of inflammation following granuloma formation. In this study, we investigated the interaction between Schistosoma japonicum eggs and neutrophils, and the effect of eggs on the inflammatory phenotype of neutrophils. Our results showed significant upregulated expression of pro‐inflammatory cytokines (IL‐1α, IL‐1β and IL‐8) and chemokines (CCL3, CCL4 and CXCL2) in neutrophils after 4 h in vitro stimulation with S. japonicum eggs. Furthermore, mitochondrial DNA was released by stimulated neutrophils, and induced the production of matrix metalloproteinase 9 (MMP‐9), a protease involved in inflammation and associated tissue destruction. We also found that intact live eggs and isolated soluble egg antigen (SEA) triggered the release of neutrophil extracellular traps (NETs), but, unlike those reported in bacterial or fungal infection, NETs did not kill schistosome eggs in vitro. Together these show that S. japonicum eggs can induce the inflammatory phenotype of neutrophils, and further our understanding of the host–parasite interplay that takes place within the in vivo microenvironment of schistosome‐induced granuloma. These findings represent novel findings in a metazoan parasite, and confirm characteristics of NETs that have until now, only been observed in response to protozoan pathogens.